Evaluation of unsulfated biotechnological chondroitin in a knee osteoarthritis mouse model as a potential novel functional ingredient in nutraceuticals and pharmaceuticals - Cimini, Donatella; Boccella, Serena; Alfano, Alberto; Stellavato, Antonietta; Paino, Salvatore; Schiraldi, Chiara; Guida, Francesca; Perrone, Michela; Donniacuo, Maria; Tirino, Virginia; Desiderio, Vincenzo; Rinaldi, Barbara (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis is a very disabling disease that can be treated with both non-pharmacological and pharmacological approaches. In the last years, pharmaceutical-grade chondroitin sulfate (CS) and glucosamine emerged as symptomatic slow-acting molecules, effective in pain reduction and improved function in patients affected by osteoarthritis. CS is a sulfated glycosaminoglycan that is currently produced mainly by extraction from animal tissues, and it is commercialized as a pharmaceutical-grade ingredient and/or food supplement. However, public concern on animal product derivatives has prompted the search for alternative non-extractive production routes. Thus, different approaches were established to obtain animal-free natural identical CS. On the other hand, the unsulfated chondroitin, which can be obtained via biotechnological processes, demonstrated promising anti-inflammatory properties in vitro, in chondrocytes isolated from osteoarthritic patients. Therefore, the aim of this study was to explore the potential of chondroitin, with respect to the better-known CS, in an in vivo mouse model of knee osteoarthritis. Results indicate that the treatment with biotechnological chondroitin (BC), similarly to CS, significantly reduced the severity of mechanical allodynia in an MIA-induced osteoarthritic mouse model. Decreased cartilage damage and a reduction of inflammation- and pain-related biochemical markers were also observed. Overall, our data support a beneficial activity of biotechnological unsulfated chondroitin in the osteoarthritis model tested, thus suggesting BC as a potential functional ingredient in pharmaceuticals and nutraceuticals with the advantage of avoiding animal tissue extraction.